Associations of Uric Acid With Liver Steatosis and Fibrosis Applying Vibration Controlled Transient Elastography in the United States: A Nationwide Cross-Section Study - Duan, Hualin; Zhang, Rong; Chen, Xingying; Yu, Genfeng; Song, Cheng; Jiang, Yuqi; He, Yajun; Wan, Heng; Shen, Jie (Frontiers in Endocrinology, 2022)
Background and objective: Serum uric acid (UA) is related to many metabolic diseases. However, the association of UA with liver diseases was not very clear. The objective of this study is to clarify the relationship of UA with liver steatosis and fibrosis. Methods: This is a cross-sectional study of 4364 people of National Health and Nutrition Examination Survey (NHANES) 2017-2018. Liver steatosis and fibrosis were assessed by controlled attenuation parameter (CAP) and liver stiffness measurements (LSM) using Vibration-controlled transient elastography (VCTE). Linear and logistic regressions were performed. Results: After adjusting for potential confounders, UA levels were associated with the prevalence of liver steatosis [OR=2.097 (95%CI: 1.254, 3.534)] and liver fibrosis [OR=2.983 (95%CI: 1.797, 4.952)]. Furthermore, the results were consistent in the subgroup analyses of males and females. Conclusions: UA levels were positively associated with the prevalence of liver steatosis and fibrosis.